Avian Reoviruses From Wild Birds Exhibit Pathogenicity to Specific Pathogen Free Chickens by Footpad Route - Choi, Yu-Ri; Kim, Sang-Won; Shang, Ke; Park, Jong-Yeol; Zhang, Jun-feng; Jang, Hyung-Kwan; Wei, Bai; Cha, Se-Yeoun; Kang, Min (Frontiers in Veterinary Science, 2022)
Avian reoviruses (ARVs) are ubiquitous in domestic poultry with 80% of them being non-pathogenic and are frequently found in clinical healthy birds. ARVs have also been known to the etiological agents of viral arthritis (VA), tenosynovitis, myocarditis, runting-stunting syndrome (RSS), and respiratory and enteric disease in chickens. Significant economic losses during the process of poultry husbandry are due, in part, to unmitigated ARV infections throughout the poultry industry. Recently, many isolates shared genetic similarities between those recovered from wild birds and those recovered from poultry by Kim et al., 2022. One explanation may be that there is a degree of spillover and spillback of ARVs between the two groups. However, studies on the role of wild birds in the epidemiology and pathogenicity of ARVs are insufficient. Here, we describe the pathogenicity in specific pathogen-free (SPF) chickens of ARV originating from wild birds. The challenge experiment was conducted in six groups including a negative control group, a positive control group (reference strain of S1133), and four groups (A15-157, A18-13, A18-205, A19-106) infected with ARVs from wild birds. The peak of clinical signs was from 3 to 5 days post infection (dpi). In addition, death of one chicken was found in the group infected with the A18-13 isolate. Reduced body weight was also found in chickens infected with ARVs from wild birds compared to the negative control group. All the ARVs infection groups showed noticeable swelling of the footpad. In addition, ARVs were detected in the bursa, tendon, and hock joint by RT-PCR in all infected groups at 5 dpi and 15 dpi. Histopathological observations revealed acute inflammatory responses on the synovium covering the joint surfaces (arthritis) and tendon sheaths (tenosynovitis), as well as bursa atrophy and lymphocyte depletion. For analysis of serum, chickens infected with ARVs showed sero-conversion. In conclusion, this study described typical severe disease of acute VA and tenosynovitis in SPF chickens infected with ARVs derived from wild birds. This study confirmed that pathogenicity of ARVs infection in SPF chickens for the first time, and these results enrich our understanding of the pathogenicity of ARVs derived from wild birds.